O repertório do constitucionalismo fraternal como manutenção de poder no cenário contemporâneo brasileiro : uma análise no âmbito público e privado - Campos, Cintia Santos (2022)
The speech readjustment analysis in order to accommodate new social, political and economic interests, that are articulated in legal dogmatics and also in international laws and treaties, presents a model that has been emerging in western democracies. This work intends to analyze the details of the interpretation of legal humanism in Brazil around these debates, which show up in the doctrines and judicial decisions, that reorganize strategies and categories to incorporate political meanings in the arguments provoked in the legal spaces around group interests. These strategies stand out by the mobilization of discourses with rights mitigation and conservation of power class. The data presented consider the recent use of interpretation in the legal doctrine of Fraternal Humanism in judicial decisions and also reflect on the use in the private scope. The analysis centralizes the discussions in the debates, as this doctrine inserts and makes inflections, suggesting the existence of a political category that would resolve, mainly, demands for collective rights, through the mobilization of a fraternal action aimed at the collectivity in the speeches. Like this the interpretation in the judgments of the Federal Supreme Court is mobilized, dealing with demands for the mitigation of rights. After that, there is an approach based on the theory of Fraternal Constitutionalism, which has similar arguments to those seen in judicial decisions, revealing an articulation of discourses around legal concepts that dialogue with an ideal of 'social justice' according to the capital, which the social actors who adhere to the theory seek to disseminate and structure in the practical world, expanding the forms of assimilation of these premises, seeking recognition and power links to explore these dynamics. The study seeksto understand the theoretical framework, itslinks and its public repercussions.